1993
DOI: 10.1002/j.1460-2075.1993.tb05975.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of NSP1 reveals complex formation with ‘GLFG’ nucleoporins and a novel nuclear pore protein NIC96.

Abstract: The essential C‐terminal domain of NSP1 mediates assembly into the nuclear pore complex (NPC). To identify components which interact physically with this yeast nucleoporin, the tagged C‐terminal domain of NSP1 (ProtA‐NSP1) was isolated by affinity chromatography under non‐denaturing conditions. The purified complex contains ProtA‐NSP1, two previously identified ‘GLFG’ nucleoporins, NUP49 (NSP49) and p54 and a novel protein designated NIC96 (for Nucleoporin‐Interacting Component of 96 kDa). Conversely, affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
235
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(240 citation statements)
references
References 46 publications
(50 reference statements)
5
235
0
Order By: Relevance
“…A second group of yeast nucleoporins that includes Nup49p, NuplOOp, Nupll6p (Wente et al, 1992;Wimmer et al, 1992;Wente and Blobel, 1994), and Nupl45p (Fabre et al, 1994;Wente and Blobel, 1994) have repeats of GLFG in their N-terminal and central domains. Nic96p (Grandi et al, 1993), a major component of the yeast NPC by mass (Rout and Wente, 1994), lacks repeats, whereas Srplp contains eight degenerate repeats that are related to repeats seen in plakoglobin, ,B-catenin, and the Drosophila armadillo protein (Yano et al, 1992(Yano et al, , 1994. A tenth yeast protein, POM152p, is thought to be a membrane protein (Wozniak et al, 1994), is not essential, and is also a very abundant component of the yeast NPC (Rout and Blobel, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A second group of yeast nucleoporins that includes Nup49p, NuplOOp, Nupll6p (Wente et al, 1992;Wimmer et al, 1992;Wente and Blobel, 1994), and Nupl45p (Fabre et al, 1994;Wente and Blobel, 1994) have repeats of GLFG in their N-terminal and central domains. Nic96p (Grandi et al, 1993), a major component of the yeast NPC by mass (Rout and Wente, 1994), lacks repeats, whereas Srplp contains eight degenerate repeats that are related to repeats seen in plakoglobin, ,B-catenin, and the Drosophila armadillo protein (Yano et al, 1992(Yano et al, , 1994. A tenth yeast protein, POM152p, is thought to be a membrane protein (Wozniak et al, 1994), is not essential, and is also a very abundant component of the yeast NPC (Rout and Blobel, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Be cause the GARl-ProtA and ProtA-NOPl fusion proteins supported cell growth at wild-type levels (data not shown), we concluded that they are fully functional. As a control, a yeast strain expressing a protein A-tagged nuclear pore protein, NSPl (Grandi et al 1993), was used. Cell extracts were prepared from each strain, and snoRNAs associated with the tagged proteins were immunoprecipitated with IgG-Sepharose.…”
Section: Yeast Aca Snornas Are Complexed With Garl But Not With Fibhlmentioning
confidence: 99%
“…Yeast strains expressing NSPl (Grandi et al 1993) son et al 1987) was PCR-amplified using sequence-specific primers (oligonucleotides 11 and 12) that introduced BamHL restriction sites at both the 5' and 3' termini. The amplified fragment was cut by BamHl and inserted into the BamHl site of pJPG67 (Girard et al 1994).…”
Section: Immunoprecipita Tionmentioning
confidence: 99%
“…Several nucleoporin subcomplexes have been identified (Grandi et al, 1993;Grandi et al, 1995a;Grandi et al, 1995b;Nehrbass et al, 1996;Zabel et al, 1996;Siniossoglou et al, 1996;Iovine et al, 1997;Bailer et al, 1998;Belgareh et al, 1998;Marelli et al, 1998;Lutzmann et al, 2002). Different nucleoporins have been localised to distinct substructures of both the vertebrate and yeast NPCs (reviewed in Stoffler et al, 1999;Doye and Hurt, 1997;Rout et al, 2000).…”
Section: Introductionmentioning
confidence: 99%